METALLOGRAPHIC COOLING RATES OF THE IIIAB IRON METEORITES - Yang J.; Goldstein J.I. (My University, 2006)
An improved computer simulation program has been developed and used to re-measure the metallographic cooling rates of the IIIAB irons, the largest iron meteorite chemical group. The formation of this chemical group is attributed to fractional crystallization of a single molten metallic core during solidification. Group IIIAB irons cooling rates vary by a factor of 6 from 56 to 338 °C/My. The cooling rate variation for each meteorite is much smaller than in previous studies and the uncertainty in the measured cooling rate for each meteorite is greatly reduced. The lack of correction for the orientation of the kamacite-taenite interface in the cooling rate measurement of a given meteorite in previous studies not only leads to large cooling rate variations but also to inaccurate and low cooling rates. The cooling rate variation with Ni content in the IIIAB chemical group measured in this study is attributable, in part, to the variation in nucleation temperature of the Widmanstatten pattern with Ni content and nucleation mechanism. However, the factor of 6 variation in cooling rate of the IIIAB irons is hard to explain unless the IIIAB asteroidal core was exposed or partially exposed in the temperature range in which the Widmanstatten pattern formed. Measurements of the size of the island phase in the cloudy zone of the taenite phase and Re-Os data from the IIIAB irons and the pallasites make it hard to reconcile the idea that pallasites are located at the boundary of the IIIAB asteroid core. ? 2006 Elsevier Inc. All rights reserved.
Keywords: COMPUTER SIMULATION; COOLING; FRACTIONAL CRYSTALLIZATION; IRON METEORITE